ALASAN TERJADINYA ALIH-KODE DALAM SERI LAYANGAN PUTUS WETV PROGRAM: (The Reasons of Code-Switching Used in the “Layangan Putus” Series, WeTV Program) - Brahmacahyani, Putu Ayu Ganitri (Uniqbu Journal of Social Sciences, 2023)
This study entitled “The Reasons of Code Switching Used in Layangan Putus Series” taken from Web Television or the name in the applications is WeTV, it has 10 Episodes and this series was published in 2021. This study interested to analyze this topic because this series took the stories related to society, this series also used Bilingual languages Indonesian and English in dialogues and it was influenced the language style of society. This study found out the reasons and analyze sociolinguistics science especially Code Switching in this series. This study aims to answer the research questions about the reasons of the characters switched their language. This study used the descriptive method, which tried to find and describe some reasons for the code-switching used by characters. This study used the theory of Hoffman (1992:116) in reasons for a bilingual person to switch their language. The type of this method for research data is also called the qualitative method because the data are collected and analyzed in words or descriptively. The results found are some reasons the characters in this series used code-switching to switch their Indonesian language to the English language, because talking about particular topics, Quoting somebody else, Being empathic about Something, Interjection, Repetition used for Clarification, Intention of Clarifying the Speech Content and Expressing Group Identity.